Creación de guías de mantenimiento en 3D para la optimización de programas de mantenimiento aplicado en la central hidroeléctrica Amoyá (2021)
This project focused on being able to carry out an analysis of the maintenance methods in ISAGEN for the implementation of its catchment maintenance plan and the generating units, where it was identified that the maintenance guides are documents of great importance for programming, planning and maintenance execution. But these documents are prepared in text formats with images or flat photographs that do not describe in a detailed way the activity to be carried out, which can be misleading due to lack of clarity. An analysis of the OMs (maintenance orders), executed from commissioning to date, was carried out to identify the behavior of the equipment and the costs associated with the different types of maintenance at ISAGEN. It was evident that there are teams with a large number of interventions, but with low costs and other teams with a low number of interventions but very high costs. As a solution to this problem, the creation of interactive maintenance guides in 3D was proposed, where the activity to be executed is represented in a very graphical way, minimizing the opportunity for errors during execution and improving maintenance planning with tighter times, identification, location, assembly of spare parts and necessary tools. With the implementation of this methodology for maintenance guides, improvements can be achieved in the indicators of maintainability, reliability, availability, and costs associated with maintenance. There will also be a very well-prepared technical document that will serve to transfer knowledge.